Extension of the spring is 6 cm
![\texttt{ }](https://tex.z-dn.net/?f=%5Ctexttt%7B%20%7D)
<h3>Further explanation</h3>
<em>Hooke's Law states that the length of a spring is directly proportional to the force acting on the spring.</em>
![\boxed {F = k \times \Delta x}](https://tex.z-dn.net/?f=%5Cboxed%20%7BF%20%3D%20k%20%5Ctimes%20%5CDelta%20x%7D)
<em>F = Force ( N )</em>
<em>k = Spring Constant ( N/m )</em>
<em>Δx = Extension ( m )</em>
![\texttt{ }](https://tex.z-dn.net/?f=%5Ctexttt%7B%20%7D)
The formula for finding Young's Modulus is as follows:
![\boxed {E = \frac{F / A}{\Delta x / x_o}}](https://tex.z-dn.net/?f=%5Cboxed%20%7BE%20%3D%20%5Cfrac%7BF%20%2F%20A%7D%7B%5CDelta%20x%20%2F%20x_o%7D%7D)
<em>E = Young's Modulus ( N/m² )</em>
<em>F = Force ( N )</em>
<em>A = Cross-Sectional Area ( m² )</em>
<em>Δx = Extension ( m )</em>
<em>x = Initial Length ( m )</em>
Let us now tackle the problem !
![\texttt{ }](https://tex.z-dn.net/?f=%5Ctexttt%7B%20%7D)
<u>Given:</u>
initial extension of the spring = x = 3 cm
initial load = F = 15 N
final load = F' = 30 N
<u>Asked:</u>
final extension of the spring = x' = ?
<u>Solution:</u>
<em>We will use </em><em>Hooke's Law</em><em> to solve this problem:</em>
![F : F' = kx : kx'](https://tex.z-dn.net/?f=F%20%3A%20F%27%20%3D%20kx%20%3A%20kx%27)
![F : F' = x : x'](https://tex.z-dn.net/?f=F%20%3A%20F%27%20%3D%20x%20%3A%20x%27)
![15 : 30 = 3 : x'](https://tex.z-dn.net/?f=15%20%3A%2030%20%3D%203%20%3A%20x%27)
![1 : 2 = 3 : x'](https://tex.z-dn.net/?f=1%20%3A%202%20%3D%203%20%3A%20x%27)
![x' = 2 \times 3](https://tex.z-dn.net/?f=x%27%20%3D%202%20%5Ctimes%203)
![\boxed {x' = 6 \texttt{ cm}}](https://tex.z-dn.net/?f=%5Cboxed%20%7Bx%27%20%3D%206%20%5Ctexttt%7B%20cm%7D%7D)
![\texttt{ }](https://tex.z-dn.net/?f=%5Ctexttt%7B%20%7D)
<h3>Learn more</h3>
![\texttt{ }](https://tex.z-dn.net/?f=%5Ctexttt%7B%20%7D)
<h3>Answer details</h3>
Grade: College
Subject: Physics
Chapter: Elasticity